LANGUAGE INTERFERENCE IN THE SOUND SYSTEM OF THE ENGLISH AND UZBEK LANGUAGES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This study investigates the phenomenon of consonant interference in the English and Uzbek languages, focusing on the similarities and differences in how consonant sounds from one language may influence the pronunciation of speakers of the other language. Through a combination of empirical data collection and theoretical analysis, we explore the patterns of consonant interference and propose potential explanations rooted in linguistic theory. Our findings shed light on the intricate interplay between phonetic systems and the challenges faced by bilingual speakers in achieving pronunciation accuracy.